Implementing Authentic Assessment in the 2013 Curriculum by English Teachers of Modern Boarding High School - Diki Atmarizon; Novita Efendi; Sherly Franchisca (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2020)
This article aimed to express the implementing authentic assessment in the 2013 curriculum by English teachers of Prof. Dr. Hamka Padang Modern Boarding High School. The illustration enclosed the kinds of authentic assessment, the implementation and the problems encountered by the English teachers. The subjects were two English teachers and 36 students. Observation checklist, questionnaire sheet and interview guideline were used as the research instruments. This is descriptive research and analyzed by qualitatively. The results showed that kinds of authentic assessment implemented by the two English teachers were oral interview, observation, writing sample, project, constructed-respond item and performance by score 45,55% with “poor category”. Although they have maximized their effort, they did not do better on the preparing, scoring, and reporting. Then, lack of time, knowledge and difficult to find appropriate material were still being problems encountered by the English teachers in implementing of the authentic assessment. Keywords: Authentic Assessment, 2013 Curriculum, English Teachers